Measurement of the B(s)0 lifetime in fully and partially reconstructed B(s)0→D(s)(-)(ϕπ(-))X decays in p¯p collisions at √s=1.96 TeV. - Aaltonen, T; Alvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Apresyan, A; Arisawa, T; Artikov, A; et al. (2011)
We present a measurement of the B(s)(0) lifetime in fully and partially reconstructed B(s)(0)→D(s)(-)(ϕπ(-))X decays in 1.3  fb(-1) collected in pp ¯ collisions at √s=1.96 TeV by the CDF II detector at the Fermilab Tevatron. We measure τ(B(s)(0))=1.518±0.041(stat)±0.027(syst)  ps. The ratio of this result and the world average B(0) lifetime yields τ(B(s)(0))/τ(B(0))=0.99±0.03, which is in agreement with recent theoretical predictions.